Meningkatkan Keterampilan Fungsional Melalui Membaca Dan Menulis Bagi Anak SD 060882 - Muniroh Rangkuti; Rahma Hayati Harahap (Pengelola Jurnal Politeknik Negeri Ketapang Jl. Rangga Sentap, Dalong Sukaharja, Ketapang 78813. Telp. (0534) 3030686 Kalimantan Barat, 2023)
Teaching Campus Activities which are a program of Merdeka Learning which aims to empower students to help improve education in various regions. One of them is the University of North Sumatra participating in the Teaching Campus Program which will be the second batch in 2023. The research location is SD NEGERI 060882 which is located on Jl. Abdullah Lubis No. 2, Upper Petisah. The title of this journal is Improving Elementary Children's Functional Skills through Reading and Writing at SD 060882. This study aims to describe how the educational process in SD is, how are the attitudes/psychology of children in the school environment and describe the process of planning, implementing and implementing the impact of research this, in order to find out how many grade 1, 2 and 3 students are not good at reading and writing and what are the factors causing children not being able to read and write. The results of the research instrument are making an Education Implementation Plan (RPP) for 4 months from March to June. And in another lesson plan there are also modules that are taught to students in grades 1, 2 and 3.